Deep TMS add-on treatment for intractable Tourette syndrome: A feasibility study. (2nd October 2016) - Bloch, Yuval; Arad, Shira; Levkovitz, Yechiel
Abstract : Objectives . In a considerable minority of patients who suffer from Tourette syndrome (TS) the disorder persists into adulthood and is associated with severe symptoms and limited therapeutic options. Repetitive transcranial magnetic stimulation (rTMS) to the supplementary motor area (SMA) has shown promising therapeutic results. Deep rTMS is a novel technology that enables deeper non-invasive cortical stimulation. This open-label pilot study is the first to examine the possible role of deep rTMS as add-on treatment for intractable TS. Methods . Twelve patients were recruited in order to examine bilateral SMA inhibition via deep TMS using the HBDL coil, as a possible treatment for adult TS treatment-resistant patients. Two patients did not complete the 20-day study protocol. Results . There were no significant side effects. While tics did not improve among the group as a whole, the subgroup of six patients with combined TS and OCD (obsessive compulsive syndrome) showed significant improvement in tic severity ( P = 0.037). Conclusions . These findings support the safety of deep rTMS for treating TS. The results also highlight the importance of studying the different TS syndromes separately (e.g., with or without OCD comorbidity) when evaluating deep rTMS protocols for TS patients.